Empowering Communities Through Partnerships: The Case of PT Unilever Sei Mangkei - Padilla Hawanda; Waizul Qarni; Aqwa Naser Daulay (Amkop Management Accounting Review (AMAR), 2025)
The purpose of this research is to find out the partnership empowerment strategy to improve community welfare in maqashid sharia review. This method uses descriptive qualitative. In this study, the data obtained directly through interviews with the person in charge of empowerment of the Unilever Indonesia Foundation (UIF), the person in charge of the perlanaan village government partnership and the local community. The implementation of this research took place at one of PT Unilever Sei Mangkei in bosar maligas sub-district, simalungun district. The analysis technique used in this research uses the Analitycal Hierarchy Process (AHP) method. The results showed that there are 2 empowerment strategies, namely the oil palm farmer program and the local MSME program. Based on the results of AHP, the highest weight of the alternative aggregate, the strategy chosen is the oil palm farmer program with a weight of 0.608. The smallholder program is in line with the principles of maqashid sharia which upholds justice, sustainability and social balance.